Local knowledge and the utilization of non-medicinal plants in home garden by the people of Donorejo Village in the Menoreh Karst Area, Purworejo, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sholekha AM, Yulia IT, Hanun Z, Perwitasari IG, Cahyaningsih AP, Sunarto, Sutarno, Sugiyarto, Buot Jr IE, Setyawan AD. 2023. Local knowledge and the utilization of non-medicinal plants in home garden by the people of Donorejo Village in the Menoreh Karst Area, Purworejo, Central Java, Indonesia. Biodiversitas 24: 645-657. Donorejo Village, in Purworejo District, Central Java, Indonesia, is one of the villages in the Menoreh Karst Mountains that uses non-medicinal plants. Donorejo villagers typically own vast plots of land that might be used for a wide range of productive purposes if planted with suitable vegetation. This study aims to investigate the knowledge of local people in the Menoreh Karst Mountain Area, Donorejo Village regarding the use of non-medicinal plants for daily life and document the use of plants by locals that can be useful to prevent delays in the transmission of local knowledge to future generations. Interviews and surveys conducted in the field using a purposive sampling strategy provided the bulk of the study's information. The age range of the 48 informants was from 25 to 91 years old, and the vast majority of them had only completed elementary school. A total of 119 species of non-medicinal plants were identified, representing 62 families and 12 different purposes, based on the results of the inventory of plants indicated by respondents and field observations. These plants were utilized as ornamental plants (48 species), food plants (44 species), cooking spices (16 species), animal feed (13 species), firewood (6 species), building materials (6 species), household items (2 species), and funeral ritual, prayer beeds, food wrapper, fence, fire starter (1 species). Based on these findings, it is clear that the residents of Donorejo Village continue to employ various non-medicinal plants in their gardens for various purposes.
Keywords: Ethnobotany, local knowledge, Menoreh karst, non-medicinal plants